2016
DOI: 10.1177/1088357615609306
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functions in Young Adults With Autism Spectrum Disorder

Abstract: Researchers have proposed that autism spectrum disorder (ASD) is characterized, at least in part, by executive function (EF) difficulties associated with the integrity of the frontal lobe. Given the paucity of research regarding EFs in young adults with high functioning ASD (HF-ASD), this research involves an examination of various indices of EF related to inhibition, planning, and generativity. Results indicate that although young adults with HF-ASD as a group met normative expectations on all measures of EF,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 85 publications
0
12
0
3
Order By: Relevance
“…Interestingly, executive functioning (inhibition and cognitive flexibility) was not related to any of the emotion coping strategies. It could be that that null findings regarding executive functioning in (high functioning) individuals with ASD can be explained by a lack in difference between individuals with ASD and typically developing peers (Brady et al 2017 ). Results in the current study however do not support this hypothesis, showing more problems in inhibitory control and cognitive flexibility in children with ASD as compared to typically developing children.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, executive functioning (inhibition and cognitive flexibility) was not related to any of the emotion coping strategies. It could be that that null findings regarding executive functioning in (high functioning) individuals with ASD can be explained by a lack in difference between individuals with ASD and typically developing peers (Brady et al 2017 ). Results in the current study however do not support this hypothesis, showing more problems in inhibitory control and cognitive flexibility in children with ASD as compared to typically developing children.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Keehn, Westerfield, Müller, & Townsend, (2017) found that children with ASD, unlike typically developing children, showed no behavioral or electrophysiological evidence of attentional capture. Geurts, Corbett, and Solomon (2009) also proposed that hyperfocus in ASD was associated with cognitive flexibility (the ability to re-allocate cognitive resources based on the situation; Brady et al, 2017;South, Ozonoff, & Mcmahon, 2007;Hill and Bird, 2006;Lopez, Lincoln, Ozonoff, & Lai, 2005). The neural correlates of cognitive flexibility in ASD are usually assessed using attention or task switching paradigms, such as the Wisconsin card sorting test (WCST; Yeung, Han, Sze, & Chan 2016) or reversal learning tasks (D'Cruz, Mosconi, Ragozzino, Cook, & Sweeney, 2016).…”
Section: Features Of Hyperfocusmentioning
confidence: 99%
“…Four out of five had experienced bullying or the feeling of being excluded in junior high school and explained that they felt "trapped" in a certain role. Thus, being given a chance to start «fresh» with new students was a positive experience, despite the notion that students with ASD have difficulties with transitions or in being flexible (Brady et al 2017). It seems as if the feeling of community was enhanced in high school.…”
Section: A Fresh Startmentioning
confidence: 99%
“…It follows then that not being part of a conversation from the beginning might enhance such challenges. Besides, challenges in cognitive flexibility might increase the need for predictability (Brady et al 2017). A larger group of people is more unpredictable than a smaller group.…”
Section: Social Challengesmentioning
confidence: 99%